2013
DOI: 10.2134/agronj2012.0500
|View full text |Cite
|
Sign up to set email alerts
|

Soil Phosphorus Effects on Forage Harvested and Nitrogen Fixation on Canadian Organic Dairy Farms

Abstract: Declining soil‐test phosphorus (STP) levels on eastern Canadian organic dairy farms is a concern because of potential negative impacts on forage growth and biological nitrogen fixation (BNF). This study examined the relationship between STP, forage productivity, and BNF on organic or transitional‐organic dairy farms in Ontario (ON) and Nova Scotia (NS). More than two‐thirds of 28 legume–grass mixed forage fields in the study were low in available P by provincial soil‐test guidelines. Averaged across all fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In many regions of Canada, low levels of bioavailable P have been reported in soils under organic management as a result of large-scale production systems and/or limited access to manure (Entz et al, 2001;Knight et al, 2010;Main et al, 2013;Martin et al, 2007;Roberts et al, 2008). The provisioning of nutrient cycling in these soils through biological activity can be an essential component of productive and sustainable organic farming systems.…”
Section: Introductionmentioning
confidence: 99%
“…In many regions of Canada, low levels of bioavailable P have been reported in soils under organic management as a result of large-scale production systems and/or limited access to manure (Entz et al, 2001;Knight et al, 2010;Main et al, 2013;Martin et al, 2007;Roberts et al, 2008). The provisioning of nutrient cycling in these soils through biological activity can be an essential component of productive and sustainable organic farming systems.…”
Section: Introductionmentioning
confidence: 99%
“…Soil test P ‐values are often low (<10 mg kg −1 ) in organic dairy systems in the cool humid region in Eastern Canada (Martin et al, 2007; Roberts et al, 2008; Main et al, 2013; Lynch, 2015). Whole farm nutrient budget analyses of 15 organic dairy farms in Ontario found a mean NaHCO 3 extractable‐P surplus of only 1 kg ha −1 yr −1 (Roberts et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…There was a lack of correlation between soil P indices and P surpluses, indicating that soil test P was not a good indicator of soil P status on these organic dairy farms. Greater than two‐thirds of 28 forage legume/grass mixed fields on organic dairy farms in Ontario and Nova Scotia were low in available soil P in a separate survey (Main et al, 2013). There was a weak correlation between soil test P and forage yield on the Canadian dairy farms surveyed by Main et al (2013).…”
Section: Resultsmentioning
confidence: 99%
“…These variations in intensity of organic management strongly impacted not only farm livestock density (livestock units ha -1 ) but also on whole-farm N, P and K nutrient surpluses and efficiencies. In more recent work on many of the same dairy farms the relationship between STP (and forage (alfalfa/grass mixtures) productivity and BNF (Main et al, 2013) showed that forage yields and BNF were not inversely related to STP levels in these long-term organically managed soils. This indicates biological and biochemical solubilization of soil organic P, and a likely enhanced role for arbuscular mycorrhizal fungi (AMF), play an important role in these systems.…”
Section: The Issue Of Phosphorusmentioning
confidence: 99%
“…A growing body of literature has reported low (<10 mg kg -1 ) soil test phosphorus (STP) levels for Canadian organic crop and livestock sectors (Entz et al, 2001;Martin et al, 2007;Roberts et al, 2008;Knight et al, 2010;Main et al, 2013). Such low bioavailable P levels suggest potential crop P deficiencies have potential to negatively impact on yields, legume biological N 2 fixation (BNF) and overall farm productivity and sustainability.…”
Section: The Issue Of Phosphorusmentioning
confidence: 99%